Healthy Living in Subsidized Houses? Evidence From Indonesia's FLPP Program - Pangeran, Adhamaski; Khoirunurrofik (Journal of Developing Economies, 2023)
Government policies to encourage homeownership rates for low-income communities (MBR) are implemented through the Housing Finance Liquidity Facility (FLPP) program, executed since 2010. However, more than half of the built subsidized homes need to meet the minimum construction standards and infrastructure requirements that can impact the health quality of their occupants. This study aims to investigate the impact of government support for purchasing subsidized housing from Indonesia's FLPP program on district/city-level public health. The results of this study indicated that the FLPP program affects home occupancy rates and the FLPP program also has a negative relationship with community morbidity levels in the MBR group. As well, state intervention in the housing sector with the FLPP subsidized housing program can demonstrably improve the quality of public health. This study recommends that the government maintain the FLPP program because, apart from increasing occupancy, it indirectly impacts health quality improvement